Computerize System For An Express Bus Company - Kang, Pin Leong (2003)
This project is regarding the implementation of management system for an express bus company. The system will use client server system to run daily operations and able to smooth up the daily operation and reduce the operation cost as well. Prior to the development of the system, a study has been done so that the organization can gain real benefits from adopting a suitable management system. So, a prototype of the system has been made to simulate the model to determine the effectiveness of the system. The prototype has been developed known as Transnasional Company Operation System (TCOS). TCOS able to control on the express bus ticketing, operation and also administration system. Moreover, migration from manual process to a computerize management system will be made more convenience to users. Information Technology infrastructure and the nature of business or activities been conducted will determine whether that system is suitable or not.